Analisa Luaran Tegangan dan Arus Listrik pada Rangkaian Panel Surya Mesin Panen Padi Mini - Herdi Susanto; Zakir Husin; Adi Sutrian; Nuzuli Fitriadi (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2020)
The design of a two-row rice harvest machine that has a weight of 65.26 kg has been designed and has worked well with a harvest speed of 20.33 hours per hectare, but the optimization of battery power to drive an electric motor needs to be studied, because the time needed to charge a battery 12 volts 45 AH to the full using a 50 watt peak solar panel is 10.8 hours considered not yet effective, so in this study optimization was carried out using two solar panel units in a horizontal position and arranged in parallel on the mini rice harvesting machine. Measurement of the output current and voltage when connected and not connected to the battery will be measured to determine the electric current received by the battery from the solar panel. The results show that the measurement data that have been made are relatively fluctuating due to weather conditions, but in general it can be concluded that the average voltage of solar panels will rise to 80% if arranged in parallel using two solar panel units and if a series of two solar panels is connected to the battery, the voltage will drop by 25%. For the condition of electric current data using one solar panel will produce an average electric current of 18 mA and if using a series of two electric panels will rise an average of 3.8 times in conditions not connected to the battery. And if it is connected to a battery using two solar panels then the electric current will drop an average of 2.8 times Keywords— voltage, current, solar panel, harvesting machine